Íons lantanídeos atuando simultaneamente como catalisadores e sondas luminescentes: inesperada clivagem seletiva da n-acetilbenzamida - Lima, Geórgia Batista Vieira de (2014)
This work reports, for the first time, the catalytic action of trivalent lanthanide ions, Ln3 +, on the cleavage of imides. In addition to accelerating the N-acetylbenzamide reaction with the nucleophile, the Ln3+ induces an unusual regioselectivity of it. The concentrations of NABZ and benzamide, investigated by gas chromatography over time, fit well to a first order kinetics, but the reactions half-life are dependent on the proportion Ln3+: imide, tending to decrease with increasing amount of Ln3+ ions. The cleavage of the Nacetylbenzamide mediated by Ln3+ ions is highly solvent dependent, suggesting that it acts as a nucleophile in the reaction. It is also dependent on the Ln3+ ion type, with the reaction rate order as follows: Yb3+ > Tb3+ > Eu3+. Unlike what occurs with the NABZ, nor phthalimide neither N-benzoyl-N-(pyridin-2-yl)benzamide undergo cleavage mediated by ions Ln3+ under the same conditions, suggesting that the reaction reported in this work is only operative with acyclic R1CONHCOR2 imides. Both Eu3+ and Tb3+ ions could be used as catalysts, as well as luminescent probes for monitoring qualitatively the N-acetylbenzamide cleavage reaction in ethanol. Finally, a mechanism consistent with the experimental observations above was proposed.